Experience with 40 cases of congenital pouch colon - Ghritlaharey R; Budhwani K; Shrivastava D; Gupta G; Kushwaha A; Chanchlani R; Nanda M (Wolters Kluwer Medknow Publications, 2007)
Aim : The aim of this study was to analyze the clinical and management aspect of congenital pouch colon. Materials and Methods : This retrospective study was carried out on 40 cases of congenital pouch colon managed in the department of paediatric surgery from 01, January 2000 to 31, December 2005. Results : The incidence of congenital pouch colon (CPC) in the present study was 11.290 % (40 of 354) of all anorectal malformations (ARM) and 19.60% (40 of 204) of high ARM. Of these 40 cases of CPC included in the study, 82.5% were male and 17.5% were female. The average age of presentation to hospital was 3.36 days with a range of 1-11 days; of these 25% patients were admitted with poor general condition. Preoperative diagnosis of CPC was possible in 75% of cases in our study. 60% ( n =24) of cases had incomplete pouch colon (Type III and IV) while 40% ( n =16) had complete pouch colon (Type I and II). Right transverse colostomy was done in 16 patients and colostomy at descending colon just proximal to pouch in two patients for incomplete (Type III and IV) CPC as a primary initial procedure. Ileostomy was done in 14 patients and window colostomy in three patients for complete (Type I and II) CPC. As definitive procedures, pouch excision and abdomino-perineal pull-through of colon was done in 17 patients, coloplasty and abdomino-perineal pull-through of coloplasty colon was done in four patients and pouch excision and abdomino-perineal pull-through of terminal ileum in four patients in our series. None of our patients underwent primary single stage procedure. Conclusion: (1) CPC comprises 11.290 % of all ARM and 19.60% of high ARM. (2) Right transverse colostomy was opted for incomplete pouch colon, while Ileostomy and window colostomy were opted for complete pouch colon as initial surgical procedures. (3) Staged surgical procedures for management of CPC were well tolerated in our series.